PWE-258 Outcomes of mesh reconstruction of perineal wounds following extralevator abdominoperineal excision of the rectum (aper). (22nd June 2015) - Ihedioha, U; Dhillon, A; Evans, J; khalil, K; Hunter, D; Kang, P
Abstract : Introduction: Extralevator APER for low rectal cancer is used to avoid the adverse oncological outcomes of inadvertent perforation and a positive circumferential resection margin associated with the conventional APER technique. Removal of the levators leaves a large defect requiring pelvic floor reconstruction. Controversy still exists on the best method of closure. The aim of this study is to present the outcomes of biosynthetic mesh for pelvic floor reconstruction. Method: Perineal reconstruction was done using biosynthetic mesh. We evaluated the short term outcomes with regards to perineal wound complications and perineal hernias. Results: 25 patients had biosynthetic mesh repairs. 23 of the patients had surgery for rectal cancer and 2 for anal cancer. Median operative time was 3.5 h. At a median follow up period of 26 months, there were 4 perineal complications (2 wound infections, 1 haematoma and 1 wound dehiscence) but no meshes were removed. 1 patient required vacuum assisted dressing for wound dehiscence. There were no perineal hernias. There was no mortality. Conclusion: The low complication rate, good outcomes in perineal wound healing and absence of perineal hernia demonstrates that use of biosynthetic mesh for pelvic floor reconstruction is safe and feasible. Disclosure of interest: None Declared.